Training vouchers, local employment agencies, and policy styles - Annabelle Doerr; Thomas Kruppe (Journal for Labour Market Research, 2015)
This paper analyzes how the policy style of local employment agencies is correlated with the award intensity of training vouchers for the unemployed – an important instrument of Active Labor Market Policy (ALMP) in Germany. We define the policy style of agencies on the basis of caseworkers' and managers' assessments regarding the voucher system and information on internal organization, cooperative and communicative behavior. We use unique survey data in combination with data on training voucher awards from the Federal Employment Agency. Our results suggest that cooperative behavior and communication have a positive influence on the intensity of training voucher awards after we control for regional and labor market characteristics.
Keywords: 330; Arbeitsagenturen; Arbeitsvermittler - Einstellungen; Bildungsgutschein